Analytical and Clinical Validation of a Plasma Fibroblast Growth Factor 21 ELISA Kit Using an Automated Platform in Steatotic Liver Disease - Makito Tanaka; Shingo Tanaka; Ryo Kobayashi; Ryosei Murai; Satoshi Takahashi (Biomolecules)
Steatotic liver disease is a global health challenge that requires reliable and noninvasive diagnostic biomarkers. This research aimed to validate the analytical and clinical performance of a fibroblast growth factor 21 (FGF21) enzyme-linked immunosorbent assay (ELISA) kit using an automated immunoassay analyzer. Plasma FGF21 levels were measured using a commercial ELISA kit on an automated immunoassay analyzer. Validation included intra- and inter-assay precision, dilution linearity, spike recovery, lower limit of quantification (LLOQ), interference testing, and sample stability analysis. Clinical evaluation involved 97 patients who underwent abdominal ultrasound-based attenuation imaging for the diagnosis of hepatic steatosis. The assay demonstrated high analytical precision, with intra- and inter-assay coefficients of variation <15% and an LLOQ of 3.260 pg/mL. Dilution linearity, spike recovery, and interference tests confirmed the reliability of the assay, whereas stability tests highlighted the minimal effect of freeze-thaw cycles and storage conditions. Clinically, FGF21 levels correlated with attenuation coefficient (r = 0.44). Diagnostic performance indicated 84% sensitivity and 81% specificity at defined FGF21 thresholds for the diagnosis of hepatic steatosis. This research confirmed the reliable analytical and clinical performance of the FGF21 ELISA kit, reinforcing its potential as a diagnostic biomarker of hepatic steatosis.